Efficacy of Warming Mung Bean Pad in Preventing Hypothermia in Transporting Newborn - Chanjaroenkij, Kanokwan (Journal of Health Science of Thailand, 2018)
Hypothermia is a common problem in newborn leading to increase morbidity. External source of heat like warming mung bean pad could be used to prevent hypothermia. The aim of this study was to evaluate warming mung bean pad in reducing hypothemia while transporting newborns, using in conjunction with standard guideline in Somdejprabuddhalertla hospital in a retrospective analytic study between January 2006 and December 2007. Based on inclusive criteria, 65 neonates were enrolled, 32 were transported under routine guideline in 2006 but each of the other 33 had a warming mung bean pad as a heat source for newborn transport in 2007. No differences in room temperatures between the two groups. The incidence of hypoglycemia was reduced from 31.25 percent to 18.18 percent. It is recommended that careful use of warming mung bean pad in conjunction with standard guideline can prevent heat loss during newborn transport.